Prevalence of early childhood caries among children attending anganwadis in Davangere City: A cross sectional survey - Puja Chandrashekar Yavagal; Chandrabhaga S Velangi; Ishita Singh; Prathmesh Desai; Christy Helen Sunny (Wolters Kluwer Medknow Publications, 2020)
Background: Early childhood caries (ECC) is a public health problem and children from low-income and minority families are particularly vulnerable to it. Aim: This study aims to assess prevalence of ECC among children attending Anganwadis in Davangere City. Materials and Methods: A cross-sectional survey was carried out among 349 children aged 2-5 years selected via cluster random sampling, attending Anganwadis in Davangere city. Caries experience was assessed using decayed missing filled teeth (dmft) index (the WHO-criteria) and ECC was recorded. IBM SPSS Statistics software version 19 was used for statistical analysis and significance level was set at P < 0.05. Descriptive data were generated in percentages. Chi-square test, Kuskall-Wallis test and Man-Whitney U-test were used for statistical analyses. Results: A total of 349 children, with mean age 3.8 ± 1.3 years, were examined. Among them, 47.7% were boys and 52.3% girls. The prevalence of ECC was 52.9%. The prevalence of ECC increased with the increasing age. It was significantly higher among 5-year-old female children compared to males (P = 0.02). The mean dmft of study population was 1.16 ± 1.54. There was only one detectable filled tooth among study population. Conclusion: The high prevalence of ECC (52.9%), along with very low prevalence of filled teeth among the Anganwadi children of Davangere city is a cause of concern. It suggests unmet dental treatment needs. Therefore, there is a need for caries preventive and treatment programs for this section of children.